Long-Term Results of Sodium 2-Mercaptoethane Sulfonate Usage on Cholesteatoma Surgery - Serdal Celik; M. Zeki Yalcın; Osman Kılıc; Mehmet Tan; Mahmut Tayyar Kalcioglu (Journal of International Advanced Otology)
BACKGROUND: Although advanced technologies and surgical procedures are used, cholesteatoma is a disease with the possibility of recurrence. The aim of this study was to determine the long-term effect of sodium 2-mercaptoethane sulfonate (MESNA) on cholesteatoma surgery.